2005
DOI: 10.1108/00400910510592220
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of ethics training on business student values

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 30 publications
0
28
2
1
Order By: Relevance
“…Some studies, however, also found lower ethical perceptions among older students (Kaynama, King, & Smith, ; Tse & Au, ). This fact may be explained by perceptions among mature students a business ethics education as being unnecessary, as it does not deliver practical, instrumental values that help reinforce their career path (Allen, Bacdayan, Kowalski, & Roy, ). In turn, work experience is not correlated to any of the (GE and OE) items that build the dependent variable—a result consistent with the recent review conducted by Lehnert et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies, however, also found lower ethical perceptions among older students (Kaynama, King, & Smith, ; Tse & Au, ). This fact may be explained by perceptions among mature students a business ethics education as being unnecessary, as it does not deliver practical, instrumental values that help reinforce their career path (Allen, Bacdayan, Kowalski, & Roy, ). In turn, work experience is not correlated to any of the (GE and OE) items that build the dependent variable—a result consistent with the recent review conducted by Lehnert et al ().…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of significance of relationships with other items generates doubts on the impact of business ethics courses on more specific or practical attitudes and abilities. For the majority of aspects that are not connected to exposure intensiveness and time , the rather discouraging results may be connected to the influence of student maturity, implying perceptions of business ethics education as unnecessary, non‐practical, and not delivering career‐boosting instrumental values (Allen et al, ; Kaynama et al, ; Tse & Au, ). Sleeper, Schneider, Weber, and Weber () propose, however, that education may change personal principles over time.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for example, ''self-respect'' is a terminal value that is personal, while ''a world at peace'' is more social in nature. However, researchers sometimes disagree as to whether certain values relate to ethics, and no consensus has yet been reached on how values map into ethical behavior (Allen et al, 2005). For example, Eaton and Giacomino (2000) classify selfrespect as a personal value because its focus is on self rather than other, whereas Fritzsche (1995) argues that self-respect relates to ethics, since one must have self-respect in order to act ethically.…”
Section: Perceptions Of Accountants' Ethicsmentioning
confidence: 99%
“…However, the results obtained from the different studies are not unanimous. Despite the fact that not all studies show a positive effect in terms of the inclusion of ethics in education on the ethical reasoning of individuals (Geiger and O'Connell 1999;Allen et al 2005), most authors come to the widespread conclusion that ethical training does have positive effects on moral reasoning and the ethics-taking process. Thus, a review of the studies carried out on 55 works by Schlaefli et al (1985) leads to the conclusion that ethical intervention influences the moral judgement of students.…”
Section: Formal Education (Years Spent In Technical Colleges/universimentioning
confidence: 94%